ANALISIS POTENSI PENGEMBANGAN USAHA PETERNAKAN SAPI PERAH DENGAN MENGGUNAKAN PARADIGMA AGRIBISNIS DI KECAMATAN MUSUK KABUPATEN BOYOLALI - Siswanto Imam Santosa; Agus Setiadi; Ratih Wulandari (Buletin Peternakan, 2013)
Population enhancement of dairy cattle could be done in a region supported by potential of its own region for the development of dairy cattle. The potencies of the region for dairy cattle enhancement could be done through provide feed availability, human resource knowledge, milk demand, income of the farmer, market infrastructure, loan institution role and local government policies. The purpose of this research was to determine the condition of the dairy farm in sub system of agribusiness in district of Musuk, and the factors that affecting the income of dairy farmers. Twenty villages in Boyolali regency were choosen as survey location. The respondents were chosen by random sampling method, with 6 respondents each village. There were 120 farmers of dairy cattle farmers were chosen in this research. Observation and direct interview methods were used to collect the data. Result of the research showed that income average of the farmers was Rp228.991,27/AU/month. Value of eficiency R/C Ratio was 1.28. Analysis of linear regression showed that age of farmer, total milk production and cost of feed significantly influence the income of dairy farmer. LQ value of dairy catlle population was 10.67 and LQ value of forage was 1.075. Analysis of SWOT showed that total score for internal external factors were 3.15 and 3.18. The result showed that dairy cattle have a potential to be developed inMusuk subdistrict. (Keywords: Dairy cattle, Sustainability paradigm, Income, SWOT, LQ)